ABOUT QUALITY OF PULSED ELECTRIC FIELDS PROCESSED MILK AND EGG PRODUCTS - Уразова , Р. (EurasianUnionScientists, 2021)
The objective of this work was to review the quality of influence of pulsed electric field processed milk and egg products. The PEF-treatment as a nonthermal method, which allows to preserve the natural quality, color, and vitamin constituents of food products.This processing is based on electroplasmolysis phenomena. Applications of PEF in food processing are discussed.